Efektifitas Media Sosial Instagram Sebagai Strategi PromosiOnline Kawasan Wisata Pacet Mojokerto - Dian Mafulla; Sudiah Hestianah; Abdul Kholik (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2022)
Indonesia is one of the countries in the world that has a lot of tourism potential,including diverse natural beauty, unique and diverse culture, and historical heritagesites. One of them is in the East Java area, precisely in the Mojokerto Pacet Tourismarea. Instagram has become a very popular social media in various parts of the worldbecause it allows users to share photographic content and follow the lives of theirfavorite celebrities. Now, Pacet tourism has an Instagram account, namely WISATAPACET TRAWAS (@wisatapacet) which currently has 8,533 followers. This accountcontains information on tourism, culinary, culture, and local wisdom of Pacet. Thisaccount is used as one of the online promotion strategies for pacing tourism. This studyaims to analyze the effectiveness of Instagram social media as an online promotion strategy for Pacet tourism and analyze the characteristics of @wisatapace Instagramcontent as an online promotion strategy for Pacet tourism. This research leads toqualitative research using library research method. Based on the results of the research,it can be concluded that social media is quite effective as a tourism area promotionstrategy because digital media users, namely Instagram, are quite in demand by internetusers. The content of @wisatapaset's content is less varied and innovative. Suggestionsthat can be conveyed from this research are for @wisatapacet Instagram contentmanagers to pay more attention to posts about Pacet tourist destinations and can beadded with Pacet culinary information or others so as to increase visitors who travel toPacet. The account manager can add a special section that holds social media to makeit more effective in promoting.